2014
DOI: 10.1093/cid/ciu619
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Patients With Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis According to Drug Susceptibility Testing to First- and Second-line Drugs: An Individual Patient Data Meta-analysis

Abstract: DST for ethambutol, pyrazinamide, and second-line tuberculosis drugs appears to provide clinically useful information to guide selection of treatment regimens for MDR and XDR tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
107
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 37 publications
5
107
1
1
Order By: Relevance
“…2). This relationship has been shown in previous studies (2,22). In addition, there were no differences in important variables related to treatment outcome, except for the higher frequency of pulmonary cavities and severe pulmonary disease on CXR in the group of patients with MICs above the CART-derived breakpoints.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…2). This relationship has been shown in previous studies (2,22). In addition, there were no differences in important variables related to treatment outcome, except for the higher frequency of pulmonary cavities and severe pulmonary disease on CXR in the group of patients with MICs above the CART-derived breakpoints.…”
Section: Discussionsupporting
confidence: 85%
“…In a univariate analysis, we found that prior TB treatment was significantly associated with both the failure to convert on sputum culture by 4 months of treatment and poor treatment outcome, highlighting the importance of appropriate treatment for MDR-TB. The relationship between the previous TB treatment and poor treatment outcome had been confirmed already in a meta-analysis (2). Additionally, indicators of disease severity, such as cavity and severe pulmonary disease on CXR, increase the risk of poor treatment outcome by inadequate penetration of the drug into the most diseased tissue due to the damaged lung parenchyma (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Estos datos evidencian la necesidad de mejorar el acceso de los pacientes a dichas pruebas, en especial, porque proporcionan información clínicamente útil para orientar la selección de los esquemas de tratamiento, aunque las posibilidades de curación disminuyen con la presencia de formas de resistencia más graves (21,22). En Colombia, la curación de los casos multirresistentes no supera el 50 %, pero no se sabe si ello está relacionado con la ausencia de pruebas de sensibilidad o con la efectividad de los esquemas de tratamiento (4).…”
Section: Discussionunclassified